Kajian Deskriptif Retrospektif Regimen Dosis Antibiotik Pasien Pneumonia Anak di RSUP. Dr. M. Djamil Padang - Dian Ayu Juwita; Helmi Arifin; Nelfa Yulianti (Jurnal Sains Farmasi & Klinis, 2017)
Pneumonia is one of acute respiratory tract infection which a major causes mortality in children and infant. The role of antibiotics in reducing morbidity and mortality this infectious disease is still dominant. Improper use of antibiotics can lead to the development of bacteria resistant to antibiotics and the occurrence of toxicity/side effects of drugs. The objective of this study was to determine the appropriateness of dosage regimen of antibiotics in children with pneumonia compared to standard literature. The study was conducted by retrospective descriptive analysis, using medical records of children with pneumonia during 2013. The results showed inappropriateness in several dosage regimen of antibiotics, such as chloramphenicol (5%), meropenem (50%), erythromycin (100%), azithromycin (100%), ceftazidime (100%), clindamycin (100%), ampicillin (100%) and gentamicin (100%). The inappropriateness of frequency of administration (administration interval) was also found in ampicillin (50%), gentamicin (20%), and cefotaxime (100%). The inappropriateness of dosage duration was found in amoxicillin (44.45%), chloramphenicol (45%), gentamicin (70%), meropenem (33.34%), ceftriaxone (66.67%), ampicillin (50%), cefotaxime (100%). While the route of administration of antibiotics was 100% appropriate.